2014
DOI: 10.1371/journal.pone.0105528
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycogen Synthase Kinase-3β Attenuates Glucocorticoid-Induced Suppression of Myogenic Differentiation In Vitro

Abstract: Glucocorticoids are the only therapy that has been demonstrated to alter the progress of Duchenne muscular dystrophy (DMD), the most common muscular dystrophy in children. However, glucocorticoids disturb skeletal muscle metabolism and hamper myogenesis and muscle regeneration. The mechanisms involved in the glucocorticoid-mediated suppression of myogenic differentiation are not fully understood. Glycogen synthase kinase-3β (GSK-3β) is considered to play a central role as a negative regulator in myogenic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
0
23
2
Order By: Relevance
“…Our observation of a concentration dependent increase in myoblast fusion and myotube formation following low dose, 25 nM and 100 nM, dexamethasone treatment is in concordance with a number of studies reporting positive effects of glucocorticoids on myogenesis in vitro [ 39 , 40 ] and muscle regeneration in vivo [ 12 , 37 ]. In contrast to our findings, Ma et al [ 79 ] reported inhibition of myogenic differentiation of C2C12 and primary mouse myoblasts following glucocorticoid treatment through the activation of glycogen synthase kinase 3β (GSK-3β). However, the concentration of dexamethasone used (10 μM) was 100–400 folds higher than our low dose treatment [ 79 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our observation of a concentration dependent increase in myoblast fusion and myotube formation following low dose, 25 nM and 100 nM, dexamethasone treatment is in concordance with a number of studies reporting positive effects of glucocorticoids on myogenesis in vitro [ 39 , 40 ] and muscle regeneration in vivo [ 12 , 37 ]. In contrast to our findings, Ma et al [ 79 ] reported inhibition of myogenic differentiation of C2C12 and primary mouse myoblasts following glucocorticoid treatment through the activation of glycogen synthase kinase 3β (GSK-3β). However, the concentration of dexamethasone used (10 μM) was 100–400 folds higher than our low dose treatment [ 79 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Ma et al [ 79 ] reported inhibition of myogenic differentiation of C2C12 and primary mouse myoblasts following glucocorticoid treatment through the activation of glycogen synthase kinase 3β (GSK-3β). However, the concentration of dexamethasone used (10 μM) was 100–400 folds higher than our low dose treatment [ 79 ]. Furthermore, with lower concentrations of 10 nM and 100 nM dexamethasone, no significant decrease in myogenin or myosin heavy chain protein expression was reported, whilst the fusion index was not assessed [ 79 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Pharmacological inhibition of GSK3β attenuates TNF-α and glucocorticoid induced suppression of MyoD expression and myotube formation in C2C12 and primary satellite cells (Ma et al, 2014, Verhees et al, 2013). TDZD-8 also improved muscle strength and Pax7 expression (a marker for satellite cells) in HSA LR mice, a mouse model of myotonic dystrophy (Jones et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of IGF‐1 or GSK3β inhibitor in differentiated C2C12 cells accelerates myogenesis shown in increased myotube formation, muscle creatine kinase (MCK) activity, and transactivation of troponin I (TnI) promoter, as well as increases the expression of MyoD, Myf5, myogenin, TnI‐slow, TnI‐fast, MCK, and myoglobin (Jl et al, ). In addition, GSK3β inhibition increases the expression of muscle regulatory protein, enhances myotube formation, and attenuates glucocorticoid‐induced suppression of myogenic differentiation (Ma, Zhong, Zheng, Shi, & Zhang, ). Here we showed that GSK3β inhibition promoted the differentiation of goat SMSCs and increased the expressions of MyoG, MyoD, MyHC1, and MyHC2a genes (Figure c‐f), suggesting that GSK3β may play important roles in goat skeletal muscle development.…”
Section: Discussionmentioning
confidence: 99%